Pengaruh Affiliate Marketing dan Live Streaming Terhadap Impulse Buying dengan Consumer Trust sebagai Variabel Mediasi - Ardianah, Sefininda Desfia; Badi'ah, Roudlotul (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The rapid growth of technology in this modern era has triggered a shift in human behavior patterns, especially in terms of shopping. This research uses consumer trust as a mediating variable to measure the impact of affiliate marketing and live streaming on impulse buying among generation Z consumers who use Shopee in Lamongan. This research uses quantitative methods. The sampling method used was non-probability sampling with purposive sampling as the sample determination method. Data was collected using a questionnaire distributed to 100 respondents. The data analysis technique used is Structural Equation Modeling- Partial Least Squares (SEM-PLS). The research results show that affiliate marketing has no effect on impulse buying, but affiliate marketing has an effect on consumer trust. Live streaming has an effect on impulse buying, but live streaming has no effect on consumer trust. Consumer trust has an effect on impulse buying. There is a mediating role from consumer trust on the influence of affiliate marketing on impulse buying, but there is no mediating role from consumer trust on the influence of live streaming on impulse buying.